Investigation of He’s Yang Chao recipe against oxidative stress-related mitophagy and pyroptosis to improve ovarian function - Miao, Chenyun; Zhao, Ying; Chen, Yun; Wang, Ruye; Ren, Ning; Chen, Bixia; Dong, Pingpei; Zhang, Qin (Frontiers in Endocrinology, 2023)
Background: Primary ovarian insufficiency (POI) is a common gynecological disease with serious ramifications including low pregnancy rate and low estrogen symptoms. Traditional Chinese medicine is regarded as an effective treatment for POI. However, the therapeutic mechanism of it is unclear. Methods: In this study, a mouse model of primary ovarian insufficiency was established by intraperitoneal injection of cyclophosphamide (CTX) and He’s Yang Chao Recipe (HSYC) concentrate was used for intragastric administration. Serum hormone levels (Anti-Müllerian Hormone, Estradiol, Progesterone, Luteinizing Hormone and Follicle Stimulating Hormone) and Oxidative Stress (OS) related products, superoxide dismutase (SOD), GSH-Px, and malondialdehyde (MDA) were measured by enzyme-linked immunosorbent assay. Pathological changes in ovarian tissue were evaluated by hematoxylin and eosin staining, and flow cytometry was used to determine reactive oxygen species content and mitochondrial membrane potential levels in granulosa cells. Mitochondrial distribution and morphology were investigated using immunofluorescence staining. The level of mitophagy was evaluated by LC3 immunofluorescence staining and autophagosome counts using electron microscopy. Western blotting and qPCR were used to detect the expression of proteins and genes related to mitophagy and the NLRP3 inflammasome. Results: After HSYC treatment, the ovarian damage was milder than in the CTX group. Compared with the CTX group; SOD, GSH-Px, and the total antioxidant capacity were significantly increased, while MDA and ROS were decreased in the HSYC treatment groups. Furthermore, mitochondrial distribution and membrane potential levels were improved after HSYC treatment compared to the CTX group. After the HSYC treatment, the LC3 fluorescent intensity and autophagosome counts were decreased. Similarly, mitophagy related markers PINK1, Parkin, LC3, and Beclin1 were decreased, while p62 was significantly increased, compared with the CTX groups. The mRNA and protein expression of NLRP3 inflammasome, NLRP3, caspase-1, GSDMD, IL-18, and IL-1β were significantly decreased in the HSYC treatment groups. Conclusion: This is the first study in molecular mechanisms underlying HSYC against granulosa cell injury in POI. HSYC protects ovaries from CTX-induced ovarian damage and oxidative stress. HSYC enhanced ovarian function in mice with primary ovarian insufficiency by inhibiting PINK1-Parkin mitophagy and NLRP3 inflammasome activation.